Pengaruh e-Service Quality dan Kepuasan terhadap e- Loyalty (Survey pada Pengguna Gopay) - Hesty Wulandari Ningsih; Indriyani Safitri; Abdul Yusuf (Business Management Journal, 2022)
Advances in technology and information that are growing rapidly require all companies to be able to create innovations to adapt to the progress of today's world. With advances in technology, competition in the increasingly fierce business world, many companies take advantage of an opportunity to create innovations that provide convenience for humans. One of them is a company in the transportation sector that creates digital-based service applications, namely GoJek, which provides payments through the GoPay feature. GoPay is one of the fintech breakthroughs from PT. GoJek utilizes advances in technology and information. The problem in this research is how e-service quality and satisfaction affect the e-loyalty of GoPay users. This study uses a casual analysis design with quantitative methods. The test equipment in this study uses the SPSS Statistic 25 and EViews 11 data processing applications involving 100 respondents as samples from GoPay users throughout Indonesia. Methods of data collection using questionnaires and literature study. The research instrument uses an interval scale. The results show that e-service quality and satisfaction have a positive and significant effect on GoPay customer loyalty.